Geological Controls on Soil Shear Strength and Slope Instability in the Watugede Sub-Watershed - Vinni Lovita; Dzikru Aminulloh; Septyo Uji Pratomo; Susilowati; Muhammad Andriansyah Gurusinga; Bambang Sulistyo; Tiara Sarastika (Acta Solum, 2026)
Landslides are a common geomorphological hazard in tropical volcanic regions, particularly in areas with steep slopes and complex geological settings. Variations in soil properties on soil shear strength across different geological formations. This study investigated the physical and mechanical properties of soils developed from the Kebobutak, Semilir, and Nglanggeran Formations and evaluated their relationship with landslide susceptibility in the Watugede Sub-Watershed. Field surveys, geological observations, and soil sampling were conducted at landslide and non-landslide sites. Soil samples were collected from two depth intervals (0-30 cm and 30-60 cm) and analyzed for soil texture, maximum water content, plasticity index, clay sensitivity, cohesion, internal friction angle, and soil shear strength. A descriptive-comparative analysis was applied to assess differences among geological formations and slope conditions. The results indicate that landslide areas generally have higher moisture content and plasticity, accompanied by lower cohesion, internal friction angle, and shear strength than non-landslide areas. Soils derived from the Semilir Formation exhibited the greatest susceptibility to landslides due to their high water-retention capacity and relatively low shear resistance, whereas soils developed on the Nglanggeran Formation showed higher shear strength and greater slope stability. These findings demonstrate that geological formations play a significant role in controlling soil mechanical behavior and slope instability through their influence on soil physical and mechanical properties. The results provide a scientific basis for landslide susceptibility assessment, slope stability modeling, hazard mitigation strategies, and land-use planning in volcanic landscapes.